The Jequié Complex Revisited: a U-Pb Geochronological Reappraisal of the Geology and Stratigraphy of the Jequié-Itagi Area (Bahia, Brazil) - Fernandes, Paulo César Dávila; Frantz, José Carlos; Rios, Débora Correia; Davis, Donald Wayne; Porcher, Carla Cristine; Conceição, Rommulo Vieira; Coelho, Rodrigo Estevam (Anuário do Instituto de Geociências, 2019)
New geological and litogeochemical data plus La-ICP-MS U-Pb isotopic study on the Jequié Complex, or Jequié “Block”, a granulite facies terrain of the Northeastern São Francisco Craton, allowed to propose that a new lithodemic unit, the Volta do Rio Plutonic Suite, should be created as a lower rank unit. The Jequié Complex is defined here as an intrusive complex metamorphosed in the granulite facies, containing an assemblage of plutonic calc-alkalic mafic to intermediate rocks, fractionated trondhjemites, tonalites and granodiorites, besides normal calc-alkaline tonalites/ granodiorites and rare metasedimentary remnants plus two different sets of leucogranites. The Volta do Rio Plutonic Suite is proposed as a lower range lithodemic unit belonging to the Jequié Complex. It is composed of granodiorites and monzogranites with porphyroclastic texture, even- -grained granitoids and fine-grained granitoids, besides an association of amphibole-bearing leucogranites and mafic to intermediate rocks. The metamorphosed mafic, intermediate and felsic rocks of the Jequié Complex compose a Cordilleran-type magnesian calc-alkalic association, which age is 2.7 Ga. In contrast, all the metagranitoids of the Volta do Rio Plutonic Suite show a distinctive ferroan (“A-type”) geochemical signature and the mafic and intermediate rocks associated to metaleucogranites show alkaline characteristics and host locally high-grade REE mineralizations contained in chevkinite group minerals. In the Volta do Rio Plutonic Suite, the porphyroclastic granites were dated at 2.6 Ga.The provisional age of alkaline mafic rocks with magmatic-hydrothermal REE mineralizations and of possibly coeval leucogranites is 2.5 Ga. These mineralizations are inedit in the world and the obtained time frame indicates the need to re-evaluate the geology and metallogenic potential of the Jequié Complex by considering its primordial igneous nature and by screening out its “granulitic” or “charnockitic” nature.